Arthroplasty Versus Internal Fixation for the Treatment of Undisplaced Femoral Neck Fractures: A Retrospective Cohort Study. (November 2020) - Afaq, Shaikh; O'Hara, Nathan N.; Schemitsch, Emil H.; Bzovsky, Sofia; Sprague, Sheila; Poolman, Rudolf W.; Frihagen, Frede; Heels-Ansdell, Diane; Bhandari, Mohit; Swiontkowski, Marc; Slobogean, Gerard P.
Abstract : Objective: To compare the 24-month risk of mortality between arthroplasty and internal fixation for undisplaced femoral neck fractures (FNFs). Design: Retrospective cohort study. Setting: Secondary data analysis of 2 multinational randomized controlled trials. Participants: Patients aged 50 years or older with a FNF. Intervention: Arthroplasty (n = 1441), including total hip arthroplasty and hemiarthroplasty, performed for a displaced FNF versus internal fixation (n = 734), including sliding hip screw or multiple cancellous screws, performed for an undisplaced FNF. Main Outcome Measurement: The primary outcome was mortality within 24 months of injury. Secondary outcomes included reoperation and health-related quality of life. Results: The 24-month mortality rate was 15.0% (n = 327). Arthroplasty was associated with a significant reduction in the odds of mortality [adjusted odds ratio (aOR): 0.56, 95% confidence interval (CI): 0.44–0.72, P < 0.01] compared with treatment with internal fixation. 11.4% (n = 248) of the study patients required reoperation within 24 months of injury. The odds of reoperation were 59% lower with arthroplasty treatment than with internal fixation (aOR: 0.41, 95% CI: 0.32–0.55, P < 0.01). The 24-month SF-12 physical component scores were 2.7 points higher in arthroplasty patients compared with internal fixation patients (95% CI: 1.6–3.8, P < 0.01). Conclusions: Our findings suggest arthroplasty for a FNF may reduce the risk of mortality and reoperation compared with internal fixation of undisplaced fractures. This finding is counter to many current surgical practices but consistent with a mounting body of evidence. Before widespread adoption of arthroplasty for undisplaced fractures, these results should be confirmed in a definitive comparative trial. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.